Genome-Wide Identification and Expression Analysis of AP2/ERF Transcription Factor Related to Drought Stress in Cultivated Peanut (Arachis hypogaea L.) - Cui, Mengjie; Haider, Muhammad Salman; Chai, Pengpei; Guo, Junjia; Du, Pei; Li, Hongyan; Dong, Wenzhao; Huang, Bingyan; Zheng, Zheng; Shi, Lei; Zhang, Xinyou; Han, Suoyi (Frontiers in Genetics, 2021)
APETALA2/ethylene response element binding factor (AP2/ERF) transcription factors (TFs) have been found to regulate plant growth and development, and response to various abiotic stresses. However, detail information of AP2/ERF genes in peanut against drought have not yet been performed. Herein, 185 AP2/ERF TF members were identified from cultivated peanut (A. hypogaea cv. Tifrunner) genome, clustered into five subfamilies: AP2 (APETALA2), ERF (Ethylene-Responsive-Element-Binding), DREB (Dehydration-Responsive-Element-Binding), RAV (Related to ABI3/VP) and Soloist (few unclassified factors)). Subsequently, the phylogenetic relationship, intron-exon structure and chromosomal location of AhAP2/ERF were further characterized. All of these AhAP2/ERF genes were distributed unevenly across the 20 chromosomes, and 14 tandem and 85 segmental duplicated gene pairs were identified which originated from ancient duplication events. Gene evolution analysis showed that A. hypogaea cv. Tifrunner were separated 3.17, 3.42, 64.07, and 66.44 Mya from A. duranensis, A. ipaensis, Medicago truncatula L., Glycine max L., respectively. Promoter analysis discovered many cis-acting elements related to light, hormones, tissues, and stress responsiveness process. Protein interaction network predicted the exitance of functional interaction among families or subgroups. Expression profiles showed that genes from AP2, ERF and DREB subfamily was significantly upregulated under drought stress condition. Our study laid a foundation and provided panel of candidate AP2/ERF TFs for further functional validation to uplift breeding programs of drought-resistant peanut cultivars.